Water mites of the genus Brachypoda (Acari: Hydrachnidia: Aturidae) in Turkey - Esen, Yunus; Pesic, Vladimir; Erman, Orhan (Magnolia Press, 2013)
In this study, three water mite species of the genus Brachypoda (Acari: Hydrachnidia: Aturidae) are reported from Turkey. Brachypoda (Hemibrachypoda) orientalis Pesic & Esen sp. nov. is characterized by the digitiform ventral extension of IV-L-4 apically bearing three peg-like setae. Populations from Russia and Turkey previously recorded under the name Brachypoda (Hemibrachypoda) mutila Walter, 1928 belong to this species. Brachypoda (Hemibrachypoda) baderi Di Sabatino & Cicolani, 1991 and Brachypoda (Parabrachypoda) montii Maglio, 1924 are reported as new for the fauna of Turkey, while Brachypoda (Hemibrachypoda) mutila Walter, 1928 is excluded from the Turkish fauna.
Keywords: Acari; water mites; running waters; Brachypoda; Turkey